Model-based approach for analyzing prevalence of nuclear cataracts in elderly residents. (November 2020) - Kodera, Sachiko; Hirata, Akimasa; Miura, Fumiaki; Rashed, Essam A.; Hatsusaka, Natsuko; Yamamoto, Naoki; Kubo, Eri; Sasaki, Hiroshi
Abstract: Recent epidemiological studies have hypothesized that the prevalence of cortical cataracts is closely related to ultraviolet radiation. However, the prevalence of nuclear cataracts is higher in elderly people in tropical areas than in temperate areas. The dominant factors inducing nuclear cataracts have been widely debated. In this study, the temperature increase in the lens due to exposure to ambient conditions was computationally quantified in subjects of 50–60 years of age in tropical and temperate areas, accounting for differences in thermoregulation. A thermoregulatory response model was extended to consider elderly people in tropical areas. The time course of lens temperature for different weather conditions in five cities in Asia was computed. The temperature was higher around the mid and posterior part of the lens, which coincides with the position of the nuclear cataract. The duration of higher temperatures in the lens varied, although the daily maximum temperatures were comparable. A strong correlation (adjusted R 2 > 0.85) was observed between the prevalence of nuclear cataract and the computed cumulative thermal dose in the lens. We propose the use of a cumulative thermal dose to assess the prevalence of nuclear cataracts. Cumulative wet-bulb globe temperature, a new metric computed from weather data, would be useful for practical assessment in different cities. Graphical abstract: Image 1 Highlights: Large-scale computation estimates lens temperature in different populations. High temperature in lens in tropical environment appears around the lens nucleus. Temperature and solar exposure correlate with prevalence of nuclear cataract. Cumulative thermal dose in lens well correlates with prevalence of nuclear cataract. Cumulative wet bulb globe temperature is proposed for practical assessment.